On the Relation between the African ITCZ and the Development of a Medicane “Scott” storm over east Mediterranean: case study - Labban, Abdulhaleem (Journal of King Abdulaziz University-Meteorology Environment and Arid Land Agriculture Sciences, 2022)
The present study investigates the role played by the African Intertropical Conversion Zone (AITCZ) in the development of Medicane Scott Landfall over Egypt during the period 21st-27th October 2019. For this, the NCEP/NCAR reanalysis of daily precipitation, geopotential height (at 500 hPa), decadal, and daily data of the AITCZ are used for October 2019. Time series analysis, anomaly, and correlation coefficient methods are used to analyze these data sets. The results reveal that there is a notable northward extension of the AITCZ, mainly over eastern Africa through the period of Medicane Scott. There is a strong significant positive correlation (0.925) between the daily precipitation over Egypt and the latitudinal position of the eastern part of AITCZ during the period of Medicane Scott. The AITCZ controls the persistence of the Rossby wave over Europe and the Eastern Mediterranean regions causing an omega-shaped block over the southern part of Europe. However, the eastern flank of this block is the Medicane Scott that landfall over Egypt which is associated with severe abnormal rainy weather over Egypt.